IW Financial Expert Survey: Fourth Quarter 2018 - Markus Demary (Institut der deutschen Wirtschaft (IW), 2018)
The experts of the IW Financial Expert Survey predict a steeper yield curve with a larger increase in long-term than in short-term interest rates by the end of the first quarter of 2019. Moreover, the average forecasts indicate higher stock market indices, a mild depreciation of the Euro vis-à-vis the US-Dollar with a larger appreciation in the first quarter of 2019. Moreover, the experts predict a larger drop in oil prices by the end of the first quarter of 2019. However, despite the expectation of higher interest rates, the short-term interest rate is predicted to remain in negative territory. The 3-month Euribor is, on average, expected to reach -0.27 percent at the end of the first quarter of 2019, while the yield on German government bonds with 10-year maturity is expected to reach 0.75 percent by then. Stock markets are, on average, expected to increase by 5.5 percent (Stoxx) and 7.6 percent (DAX) by the end of the first quarter of 2019. During that same period, the experts predict a mild depreciation of the Euro by 0.4 percent vis-à-vis the US Dollar by the end of the year followed by an appreciation of 1.6 percent by the end of the first quarter of 2019. In addition to that, the experts predict oil prices to drop by 7.3 percent in the forthcoming six months. The expectation of an increase in the long rate and a slight increase in the short rate hints at a financial market outlook characterised by a cautious approach to monetary normalisation. In this cautious approach, the ECB lets the market determine the first increases in long-term interest rates before it stops intervening at the long end of the yield curve, while keeping the short end of the yield curve lower. This cautious approach to monetary policy normalization is reflected in the projection of the yield curve. Moreover, the experts expect that the development of the Euro and the development of oil prices as well as the development of the stock market will support the ECB's cautious approach to monetary normalization instead of forcing a faster exit from low interest rates. These expectations are in line with the experts' view on the ECB's forward guidance. Most experts expect the ECB to state at its December 2018 press conference that it expects inflation to converge towards the policy objective of an inflation rate of lower, but close to 2 percent. Moreover, they expect the ECB to state that monetary policy stimulus is still necessary for reaching its policy target. The experts agree that the key policy interest rates will remain at their current levels at least until the summer of 2019 as highlighted by the ECB and most of the surveyed experts expect the ECB to end net asset purchases by the end of the year, but also to reinvest the principle payments from maturing securities. The evaluation of the forecasting performance of the latest forecasts yielded the result that Commerbank and Hamburger Sparkasse performed best in predicting trends in the long-term ranking, which covers all forecasts from June 2014 to June 2018. When it comes to point prediction, in the long-term evaluation of the period running from June 2014 to June 2018, the experts of National-Bank performed best in predicting all indicators.
Keywords: G12; G17; 330